Pattern of occupant injury for real frontal crashes in malaysia - Nur Fatihah, Jeffri; Hanida, Abdul Aziz; Mimi Nabila, Mohd Noordin (2021)
More than 8.2 million police reported motor vehicles crashed, resulting in 67,882 fatalities and over 140,000 injured victims from 2009 to 2018 recorded by Ministry of Transport, Malaysia. Many accidents reported involving with passenger vehicles including driver’s injury were due to frontal accidents.